2020
DOI: 10.1088/1755-1315/418/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Yield and fruit morphology of selected high productive Papua nutmeg trees (Myristica argentea Warb.)

Abstract: Fakfak nutmeg is also known as Papua Nutmeg, and has become one of the main income sources of local communities in Fakfak and Kaimana Districts. It produces butter nutmeg, a fat derived from the seed used in perfumery and soaps. It grows wild or semi cultivation, so the productivity is generally low. To improve productivity, it is necessary to use planting materials derived from high productive trees. The study was aimed to identify nutmeg trees with high yield, good quality of fruit, seeds and essential oils.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
3
0
2
Order By: Relevance
“…Besides, other research confirmed that Banda Sangihe nutmeg has seed weight 6.9 -9.5 g/grain. The size and nutmeg yield found high variation among plantations in Indonesia related to varieties, seasonal weather, and cultivation practices [8]. However, the nutmeg seeds in the research have perfectly shaped, relatively heavy, not attacked by pests and diseases, and did not get mechanical damage.…”
Section: A the Quality Of Raw Materials And Yield Of Nutmeg Oleoresinsmentioning
confidence: 76%
See 1 more Smart Citation
“…Besides, other research confirmed that Banda Sangihe nutmeg has seed weight 6.9 -9.5 g/grain. The size and nutmeg yield found high variation among plantations in Indonesia related to varieties, seasonal weather, and cultivation practices [8]. However, the nutmeg seeds in the research have perfectly shaped, relatively heavy, not attacked by pests and diseases, and did not get mechanical damage.…”
Section: A the Quality Of Raw Materials And Yield Of Nutmeg Oleoresinsmentioning
confidence: 76%
“…Nutmeg seeds contain essential oils and fatty oils, depending on the origin of the raw material. Other study revealed the result of 3.11-3.91% essential oils and 14-15% oleoresin of nutmeg seeds from Papua [8]. Generally, the essential oil content of nutmeg seeds from Papua is much lower than the essential oils of Banda nutmeg seeds.…”
Section: E Nonvolatile Content and Chemical Composition Of Nutmeg Oleoresinsmentioning
confidence: 92%
“…Kandungan senyawa kimia yang terdapat pada suku Zingiberaceae berpotensi sebagai antioksidan, antibakteri, antivirus termasuk Covid 19 dan antiinflamasi yang dapat dijadikan sebagai bahan baku obat yang bernilai ekonomis tinggi (Nogueira et al, 2019). Senyawa dari suku Zingiberaceae dapat menghalangi Covid 19 dikarenakan senyawa bioaktif gingerol yang terkandung di dalam minyak jahe memiliki efek sebagai anti-inflamasi, antipiretik, gastroprotective, cardiotonic dan antihepatoksik terhadap virus Covid 19 pada masa pandemi (Wahyuni & Bermawie, 2020).…”
Section: Gambar 41 Jenis-jenis Tanaman Obat Berdasarkan Familyunclassified
“…Another genus myristica that has a big fruit size is M. argentea Warb or Papua nutmeg. The fruit weights of the selected mother trees of Papua nutmeg vary from 93 -105 g with a fruit length of 6.5-7.9 cm and fruit width 4.3-6.2 cm[8].…”
mentioning
confidence: 99%